Implementing part-time leadership as instrument for sustainable HR management - Anja Karlshaus (International Journal of Corporate Social Responsibility (JCSR), 2020)
This paper discusses the suitability of part-time leadership as instrument for a sustainable Human Resources Management (HRM) policy. The concept of part-time leadership is introduced and discussed based on a meta-analysis of existing studies and latest research that has been executed on' atypical'working time arrangements in leadership positions. The article discusses the intersection of part-time leadership with the three subject areas (economic, social and ecological) of the Triple-Bottom Line and tries to show more specifically how part-time leadership models can serve the fulfillment of selected Sustainable Development Goals (SDGs), especially in Western countries. Finally, prerequisites and common barriers for a successful implementation of part-time leadership as Corporate Social Responsibility (CSR) instrument of organizations are unveiled, and suggestions for mitigating those challenges are given from a macro, micro and process perspective.
Keywords: 650; Part-time leadership; Atypical working time arrangements; Working time models; Sustainable HRM; Triple bottom line; Sustainable development goals